Evaluation of Ethical Dilemmas and Business Sustainability in Maintaining a Company's Reputation in Global Markets - Yendra; Zakaria, Zakaria (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study examines the intersection of ethical dilemmas and business sustainability in influencing corporate reputation in global markets. It investigates how companies navigate ethical challenges while maintaining stakeholder trust and achieving long-term sustainability. The study employs a systematic literature review (SLR) approach, synthesizing insights from peer-reviewed articles, industry reports, and empirical studies published after 2018. Using Stakeholder Theory and the Environmental, Social, and Governance (ESG) framework as guiding concepts, the research analyzes how ethical considerations shape corporate reputation and sustainability strategies. The findings reveal that companies prioritizing ethical business practices and sustainability frameworks, such as ESG, are better positioned to protect their reputation and enhance stakeholder trust. Ethical dilemmas commonly arise in supply chain management, labor practices, misleading marketing, and environmental responsibility. Companies that neglect these principles face reputational damage, consumer backlash, and regulatory penalties. In contrast, businesses that integrate sustainability into their core strategies safeguard their reputation, achieve competitive advantages, and foster long-term growth. This study highlights the importance of embedding ethical considerations into business operations, emphasizing stakeholder engagement, transparent supply chains, and ESG implementation. The research offers practitioners actionable insights to develop robust sustainability frameworks that mitigate reputational risks. Future research should explore industry-specific challenges and the role of technology in enhancing ethical business practices.